DIAGNOSIS RELATED GROUP MIGRATION AS AN INDICATOR OF A POTENTIALLY INEFFICIENT MEDICAL INTERVENTION - Topalovic, Marina; Milosevic, Mirjana; Zorica Terzic - Supic, Zorica; Todorovic, Jovana; Santric Milicevic, Milena (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Diagnosis related group migration (DRG) is a phenomenon in coding hospitalizations that indicates that a patient has been transferred from one group to a different, more costly group, after an episode of hospital treatment, solely because of complications or comorbidities that occurred during hospitaltreatment or medical intervention.Objective: The objective of the study was to examine the following: occurrence of DRG migrations, hospital costs, and length of hospitalization for colectomies.Methods: A retrospective secondary analysis of DRG data was conducted for a series of episodes of hospital treatment (n = 4,939) in patients aged 18 and above, who underwent colectomy in 49 hospitals in the Republic of Serbia, in the period between 2018 and 2020, and whose episodes of hospital treatment were grouped into three diagnosis related groups: the G02A group, a separate G02A group with T81-T88 diagnoses for surgical treatment complications, and the G02B group.Results: In the observed three-year period, the incidence of DRG migration was 7.4%. Inpatient treatment of patients classified in the diagnostic group G02A (T81-T88), which represents DRG migration, was statistically significantly more costly and these patients had a statistically significantly longer hospital stay. Thetotal invoice amount for the diagnostic group G02A (T81-T88) was 509,651.7 dinars (approximately 4,320 euros), and the average length of an episode of hospital treatment was 23 days. In group G02B, the total invoice amount was 231,989.0 dinars (approximately 1,960 euros) with an average length of hospital stay of 11 days.Conclusion: Colectomies with complications prolong the length of hospitalization and imply a higher consumption of resources in the Republic of Serbia. Cost analysis related to DRG migration, per patient day and patient, may indicate the ineffectiveness of medical interventions.
Keywords: DRG migration; colectomy; cost; hospitalization; Serbia